The Concept Of Reconstructionalism Education In The Preparation Of The Educational Curriculum - Nova Junaeni (STIT Attaqwa, 2023)
In the context of educational philosophy, reconstructionism is a movement that seeks to overhaul the old system and build a modern structure of cultural life. Through institutions and educational processes, reconstructionism wants to dismantle the old order and build a completely new order of cultural life. With a combination of a critical attitude, breadth of insight and moral sensitivity, critical pedagogy can then become an inspiration for education to encourage social involvement and bring about change in society. The school curriculum must not be dominated by the majority culture or by a culture that is determined or preferred because all cultures and related values have the right to have a place in the curriculum. Teachers must show true or sincere respect for all cultures both in teaching and in teaching. other.